2014
DOI: 10.1002/cncr.28565
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor FokI gene polymorphisms may be associated with colorectal cancer among African American and Hispanic participants

Abstract: BACKGROUND: Vitamin D plays a role in cancer tumorogenesis and acts through the vitamin D receptor (VDR). Although African Americans have the lowest serum vitamin D levels, supplementation has not yielded a significant improvement in cancer. Gene polymorphisms in VDR may play a role. There is a dearth of information on VDR gene polymorphisms and colorectal cancer (CRC) among under-represented ethnic groups. In this study, the authors examined whether VDR gene single nucleotide polymorphisms (SNPs) were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
6
33
0
Order By: Relevance
“…In line with us Hughes et al26 could not provide any significant effect between TaqI polymorphism and susceptibility to sporadic CRC in Czech population as well. Another consistency with our study approved by Sarkissyan et al19 which they showed VDR TaqI polymorphic variants were not associated with CRC in their population. Also, Heather Ochs-Balcom et al 18 did not observe significant associations between TaqI SNP and colon cancer in their analysis.…”
supporting
confidence: 92%
“…In line with us Hughes et al26 could not provide any significant effect between TaqI polymorphism and susceptibility to sporadic CRC in Czech population as well. Another consistency with our study approved by Sarkissyan et al19 which they showed VDR TaqI polymorphic variants were not associated with CRC in their population. Also, Heather Ochs-Balcom et al 18 did not observe significant associations between TaqI SNP and colon cancer in their analysis.…”
supporting
confidence: 92%
“…Pibiri et al [21] reported that single nucleotide polymorphisms in vitamin D-related (VDR) genes could minimally affect CRC susceptibility in African Americans based on their study of 961 African American CRC cases and 838 healthy African American controls. In comparison to Hispanic Americans (a population with lower CRC risk when compared to Caucasians), Sarkissyan et al [22] evaluated the association between VDR gene single nucleotide polymorphisms (SNPs) in VDR (FokI, BsmI, TaqI, and ApaI) and CRC risk. The authors compared 78 patients with CRC (cases) with 70 patients with polyps and 230 polyp-free controls.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, VDR single nucleotide polymorphisms (SNPs) have been implicated in CVDs and various cancer susceptibilities in AAs (Beydoun et al, 2018;Beydoun et al, 2017;Y. C. Li, 2013;Mishra et al, 2013;Sarkissyan et al, 2014). Our findings suggest that VDR upregulation may ameliorate some of the effect of lower plasma 1,25(OH)2D levels, while SNPs within VDR have profound effects because they exacerbate an already deficient vitamin D environment in AAs.…”
Section: Discussionmentioning
confidence: 65%